Pengaruh Aksesibilitas Suasana Promosi Terhadap Kepuasan Pelanggan Kopi Kenangan Margonda Raya - Roma Ito Pasaribu; Jamaludin Khalid (Yayasan Literasi Sains Indonesia, 2023)
The culture of drinking coffee is starting to be favored by people in Indonesia, both young and old. Coffee is a brewed drink that has been known to the public since the 9th century. Coffee shop is a hangout place for young people. Coffee is a drink that has many benefits, especially for the health of the body. Coffee can promote weight loss, increase energy, protect the liver and prevent brain disease. Currently, coffee shops are competing to create delicious flavors, unique variants and even provide toppings with various flavors. Companies must be able to understand what their customers need, in order to create a sense of satisfaction with the products purchased. The research aims to determine whether there is an effect of accessibility, atmosphere, and promotion on customer satisfaction of Kopi Kenagan Margonda Raya. The research population is consumers who have purchased Margonda Raya Coffee Memories with an unknown population size. The sample in this study was 120 respondents based on the accidental sampling method. The analysis technique used in this study is multiple linear regression analysis. The results of the study illustrate that accessibility, atmosphere, and promotions have a positive and significant impact on customer satisfaction of Kopi Kenangan Margonda Raya.